Social isolation: an integrated molecular web that disrupts cellular homeostasis - Qaisiya, Mohammed; Moretto, Edoardo; Battocchio, Elisabetta; Pistella, Aurora; Caso, Maria Giuseppa; Bellani, Marcella; Guarnieri, Fabrizia Claudia (Frontiers in Neuroscience, 2025)
Social isolation and perceived loneliness are increasingly recognized as serious public health concerns, with extensive evidence linking them to adverse mental and physical health outcomes. Defined, respectively, as the objective lack of social interactions and the subjective feeling of insufficient connection, both conditions are present across various age groups and are associated with elevated risks of cognitive decline and psychiatric disorders. Epidemiological studies have also identified a strong association between chronic social isolation and the development of metabolic syndrome (MetS) and cardiovascular diseases (CVD), potentially mediated by dysregulated stress responses, immune function, and endocrine signaling. Animal models of social deprivation have proven instrumental in elucidating the biological underpinnings of these effects, revealing disruptions in neurotransmitter systems and in the hypothalamic–pituitary–adrenal (HPA) axis, with important downstream metabolic alterations. This review explores the molecular and cellular mechanisms linking social isolation to MetS and CVD, with a focus on oxidative stress, inflammation, mitochondrial dysfunction, and impaired autophagy. A deeper understanding of these pathways is essential to guide the development of targeted interventions and to reduce the long-term health burden associated with social disconnection.